Valoración de impactos de la construcción hidroeléctrica El Quimbo con los indicadores de sostenibilidad, en el caso de la vereda El Espinal y vereda Nuevo Veracruz en Gigante, Huila (2021)
The content of this research exposes the results of the study carried out in Gigante municipality, which shows the effects caused in the productive, vial, social and environmental part of the municipality by the negative impacts from the construction of the El Quimbo hydroelectric plant located in the central part of the Huila Department. Therefore, the research is based on the collection of information and detailed analysis in order to apply sustainability indicators to assess the level of sustainability in some of the affected villages in the municipality. A specific legal framework is taken into account to provide timely follow-up to the needs, deficiencies or opportunities analyzed by means of field observation instruments to understand the needs of the sector, where knowledge about the negative impacts of a regional infraestructure project, a global frame of reference that reveals in advance the elements that make up the characteristics of Quimbo. From this case, it is shown how these decisions generate changes in the previous conditions of life of especially rural populations, to which a strategic plan is proposed based on the greatest problem impacted in the area of the region, finally making a compilation of the data and solution proposals in the investigation an information booklet.